CXCL13 is elevated in inflammatory bowel disease in mice and humans and is implicated in disease pathogenesis - Liu, Ting; Liu, Yu; Liu, Chen-xi; Jiang, Yong-mei (Frontiers in Immunology, 2022)
CXCL13 is a chemokine that is widely involved in the pathogenesis of autoimmune diseases, tumors and inflammatory diseases. In this study, we investigate the role of CXCL13 in the pathogenesis of inflammatory bowel disease using both clinical specimens and animal models. We found that the serum CXCL13 concentration in IBD patients was significantly higher than that in healthy controls, and correlated with that of CRP, neutrophils counts and hemoglobin. The increase of CXCL13 in IBD patients might be related to the significant decrease of circulating CD4+CXCR5+ T cells, the increase of CD19+CD5+ B cells and the enhancement of humoral immunity. In mice colitis model, we also found elevated levels of CXCL13 in colon tissue. Cxcl13-/- knockout mice exhibited a mild, self-limiting form of disease. Additionally, CXCL13 deficiency restricted CD4+CXCR5+ T cells migration in mesenteric lymph nodes, resulting locally regulatory B cells increased in colon. In conclusion, our findings raise the possibility that CXCL13 plays a critical role in the pathogenesis of IBD. We believe that our findings will contribute to the understanding of the etiology, and that antagonizing or inhibiting CXCL13 may work as a potential adjunctive therapy strategy for patients with IBD.